Pembinaan Anti Hoaks Bagi Masyarakat Kampung Sanggaria Arso 1, Distrik Arso Barat, Kabupaten Keerom, Propinsi Papua - Nurjayanti Nurjayanti; Masni Sanmas (Madani: Jurnal Pengabdian Masyarakat dan Kewirausahaan, 2023)
The society of Sanggaria Arso 1 village, Arso Barat subdistrict, Keerom district, Keerom province majority are transmigrant people with various work backgrounds, among them are farmers, traders, ranchers, private employees and civil servants and housewives. The society of Sanggaria village have been facilitated by a stable internet network infrastructure and encourage the society to adapt with advances information and communication technology, include understanding the use of smartphones in everyday life. Through smartphones, people are getting to know various types of social media and chat applications which are a source of information for the society, including information that is not yet clear. So the purpose of this activity is to provide guidance to the society so that they are able to trace the truth of an information for the sake of creating a safe and peaceful society environment. The method of implementing this activity begins with conducting a feasibility study and mapping the needs of the Sanggaria village community, then planning a program that is adjusted to the participant’s time, compiling material, implementing the program, and ends with an evaluation of coaching activities. This activity begins with the presentation of material about the four pillars of digital literacy, followed by material about hoaxes, how to track hoaxes, simulations of tracking the truth of information and closed with an explanation of related legal approaches contained in the law on electronic information and transactions (UU ITE). The results obtained through this activity are the understanding and ability of the community to track information so that they are able to classify true information and hoaxes.